Autentisitas, Identitas Digital, dan Validasi Komunitas: Konstruksi Kepercayaan Generasi Z terhadap Influencer Marketing di Era Kecerdasan Buatan - Amirudin Amirudin; Syabrina Fitriyani (LAP4B, 2026)
This study aims to explore and understand the process of consumer trust construction among Indonesian Generation Z toward influencer marketing practices increasingly mediated by artificial intelligence (AI). Amid the proliferation of AI-algorithm-supported digital content, fundamental questions about how trust is built, maintained, and even dismantled in technology-based influencer ecosystems have become increasingly critical. This study employs an interpretive phenomenological approach with data collection through semi-structured in-depth interviews with 18 Generation Z informants (aged 18–27 years) who actively consume social media content in Indonesia. Data analysis was conducted through Interpretative Phenomenological Analysis (IPA) procedures, yielding three main themes: (1) the dualism of trust between authenticity and suspicion of AI-based content; (2) the construction of influencer digital identity as a trust proxy; and (3) community mediation as a social validation mechanism. Findings reveal that Generation Z possesses digital literacy enabling them to detect AI-based manipulation, yet paradoxically maintain loyalty to influencers perceived as authentic even when using AI tools. This research contributes to the development of digital trust theory and provides practical implications for marketers in designing ethical and transparent influencer marketing strategies in the AI era.